The Relationship Between Knowledge and Behavior Regarding COVID-19 Prevention among Elderly - Silvia Clara Laturette; Shinta Novelia; Siti Syamsiah (Nursing and Health Sciences Journal (NHSJ), 2023)
The process of getting old will continue to occur and cause various morphological changes that affect the function of the respiratory system. The respiratory system in the elderly shows a structural and functional decline, resulting in increased respiratory work compared to other young people. This is associated with a decreased ability when suffering from mother acute diseases such as heart defects, bacterial or viral infections, and blockages in the airway. The risk of complications from COVID-19 is higher in some vulnerable populations, especially the elderly and individuals who suffer from weakness or have some chronic conditions. The risk of death increases with age and is also higher in those with diabetes, heart disease, blood clotting problems, or who have shown signs of sepsis. The purpose of this study is to determine the relationship between Knowledge and COVID-19 Prevention Behavior in the Elderly This type of research is quantitative research. The population is all elderly in the working area of Piru Health Centre, which consists of 123 people. The sample consisted of 94 people selected by simple random sampling. Research instruments are questionnaires of knowledge and behavior. Data analysis is performed univariately and bivariate using the chi-square test. The results showed a significant relationship between knowledge and COVID-19 prevention behavior in the elderly in the Piru Health Center Work Area. Knowledge influences the behavior of the elderly health, so it is hoped that the government can provide Health Education to improve the understanding of the elderly to improve COVID-19 prevention behavior.